Differentiating analogous tRNA methyltransferases by fragments of the methyl donor - Lahoud, Georges (Cold Spring Harbor Laboratory Press, 2011)
Bacterial TrmD and eukaryotic-archaeal Trm5 form a pair of analogous tRNA methyltransferase that catalyze methyl transfer from S-adenosyl methionine (AdoMet) to N(1) of G37, using catalytic motifs that share no sequence or structural homology. Here we show that natural and synthetic analogs of AdoMet are unable to distinguish TrmD from Trm5. Instead, fragments of AdoMet, adenosine and methionine, are selectively inhibitory of TrmD rather than Trm5. Detailed structural information of the two enzymes in complex with adenosine reveals how Trm5 escapes targeting by adopting an altered structure, whereas TrmD is trapped by targeting due to its rigid structure that stably accommodates the fragment. Free energy analysis exposes energetic disparities between the two enzymes in how they approach the binding of AdoMet versus fragments and provides insights into the design of inhibitors selective for TrmD.